FORMATION OF A MODEL FOR MANAGING THE POTENTIAL OF REGIONAL MARKETS - Tetiana Savchenko; Olga Rodina; Olena Nikoliuk (Baltic Journal of Economic Studies, 2024)
In an unstable and rapidly changing economic environment, it becomes even more difficult to determine the state and prospects of development of specific markets, especially regional ones, where specific conditions are in place. In order to effectively coordinate the development of a particular regional market, it is necessary to clearly define the extent to which its potential has been exploited and to identify the factors that influence the formation of the regional market's potential. The subject of the study is the theoretical and methodological foundations of managing the potential of regional markets. The aim of the study is to develop a model for managing the potential of the regional market. Methodology. To achieve the goal of the study, the following tasks were set and solved: a critical analysis of approaches to the definition of the concept of "regional market potential" was carried out, the theoretical and methodological foundations for the formation of a model for managing the potential of the regional market were substantiated, the components of this model were clarified, and the types of links between the components of the model for managing the potential of the regional market were identified. The paper uses the following methods and approaches to research: abstract and logical approach used in the study of the theoretical and methodological foundations of interaction management, analysis of theoretical approaches to the formation of a model for managing the potential of the regional market, inductive and deductive (used to determine the factors influencing the formation of a model for managing the potential of the regional market), systematisation and generalisation (to clarify the concept of "regional market potential"). Results. The research considers the processes of formation and management of the potential of regional markets. It reveals the essence of the concept of "potential of the regional market" on the basis of studying the definition of the concept of "potential". The article describes and groups approaches to determining the market potential of a region and formulates its own definition of the regional market potential as "the upper limit of production, sales and consumption of a certain type of product in the region, at which the financial interests of market participants are maximally satisfied, for which the existing resources are sufficient". The publication identifies the factors influencing the state of the regional market potential: industrial capacities, development of regional infrastructure and logistics, demographic situation, population income and purchasing power, resource provision of the region, opportunities for international trade. The article characterises the structure of the regional market potential: the forming component (production, consumer and trade potential) and the ensuring component (socio-economic potential of the region). A model of management of the regional market potential is proposed. Practical implications. The proposed model will help to clarify the role and functional relationships between the components of the regional market potential and take into account the peculiarities of the functioning of regional markets in the implementation of market forecasts. Value/originality. In the structure of the regional market potential, unlike the well-known ones, the forming and ensuring components of the regional market potential are distinguished. The addition of the trade potential component to the traditional forming components, such as consumer and production potential, will allow taking into account trade opportunities and conditions for fast and high-quality trade organisation in the region.